SOLASODINE STEROID BIOCONVERSION BY MYCOBACTERIUM PHLEI DSM 43286. - S. Pudjiraharti; T. A. Budiwati; J. Kantasubrata; A. T. Karossi (Jurnal Kimia Terapan Indonesia, 1992)
Bioconversion of solasodine by Mycobacterium phlei DSM 43286 was conducted to obtain intermediate compounds which might be used as precursor in the production of steroidal drugs, i:e androst-4-en-3, 17-dione (AD) and androsta-l,4-diene-3,17-dione (ADD). M. phlei was firstly grown in nutrient broth medium at 37 °C for 8.5 hours with agitation of 200 rpm. The bacterial culture thus obtained was used as starter to inoculate the conversion medium containing 0,02% solasodine as the substrate and 0.01% 8-hydroxyquinoline as inhibitor. Bioconversion was conducted for 12 days at 37 °C using the same speed of agitation. Analysis of the bioconversion products was carried oUl using samples taken periodically at a 24-hour interval by TLC and HPLC methods. TLC analysis using chloroform-ethyl acetate (80:20) as eluent, measurement of the nuvamum wavelength and molar extinction coefficient value showed that AD and ADD was not found in the fermentation product,, but other intermediau: compound might the present. However, HPLC analysis of the fermentation products using Ik'Porasil column and benzene- ethylacetatechloroform (40:80:10) as eluent, showed -peaks with retention time similar to that of AD (during the 2nd - 9th day of incubation) and, ADD (during the 5th - 6th day offermentation) and, other unknown peaks.